2011
DOI: 10.1016/j.rmed.2010.09.020
|View full text |Cite
|
Sign up to set email alerts
|

The cost of COPD exacerbations: A university hospital – based study in Greece

Abstract: The cost estimation of severe exacerbations is important as it could trigger further research and also provide the opportunity of creating national epidemiological and economic data. Such data could contribute to the estimation of the total economic and societal burden of COPD in the country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 36 publications
2
40
1
1
Order By: Relevance
“…Another phenomenon is the challenge of changing prescribed drugs to generics, otherwise patients have to bear the cost on their own [13,87,95,102,105]. Hence, serious adverse events lead to higher costs due to disease complications [13,106,107]. However, MITSIKI et al [35] have reported that newly diagnosed COPD cases present a better compliance to treatment than the known COPD group.…”
Section: Treatment Adherence During Crisismentioning
confidence: 99%
See 4 more Smart Citations
“…Another phenomenon is the challenge of changing prescribed drugs to generics, otherwise patients have to bear the cost on their own [13,87,95,102,105]. Hence, serious adverse events lead to higher costs due to disease complications [13,106,107]. However, MITSIKI et al [35] have reported that newly diagnosed COPD cases present a better compliance to treatment than the known COPD group.…”
Section: Treatment Adherence During Crisismentioning
confidence: 99%
“…Currently, it has been supported that about half of COPD exacerbations constitute severe exacerbations [13,106], which poses a significant economic burden on society. More specifically, nowadays it is estimated that per severe exacerbation €1711 will be spent and only €621 will be reimbursed by social security funds [106]. Additionally, the cost has been shown to increase in a linear fashion in the case of advanced disease (GOLD grades A-D) [41,106].…”
Section: Economic Burden Of Copd Exacerbations During the Greek Crisismentioning
confidence: 99%
See 3 more Smart Citations